2016
DOI: 10.22159/ajpcr.2016.v9i5.13476
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of in Vitro Antimicrobial Activity and TLC Studies of Petals of Selected Indian Medicinal Plants

Abstract: Objective: The present study was to evaluate the in vitro antibacterial activity, and thin-layer chromatography (TLC) studies from the petals of fourdifferent Indian medicinal plants (Punica granatum, Hibiscus rosa-sinensis, Cassia auriculata, and Moringa oleifera).Methods: The phytochemical screening of the methanol extract of petals of four different Indian medicinal plants was performed using standardprocedures. The antimicrobial activity was tested against various test organisms using the agar disc diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
2
1
1
Order By: Relevance
“…Alkaloids were not detected in M. oleifera and V. karroo but only in C. tagasaste. These results are in contrast with Rengarajan, Melanathuru [68] who found that M. oleifera contained alkaloids among other phytochemicals. It is not immediately clear why none of the analysed phytochemicals were not detected in V. karroo vermicompost in this study.…”
Section: Microbial and Earthworm Populations In Vermicompostscontrasting
confidence: 93%
See 2 more Smart Citations
“…Alkaloids were not detected in M. oleifera and V. karroo but only in C. tagasaste. These results are in contrast with Rengarajan, Melanathuru [68] who found that M. oleifera contained alkaloids among other phytochemicals. It is not immediately clear why none of the analysed phytochemicals were not detected in V. karroo vermicompost in this study.…”
Section: Microbial and Earthworm Populations In Vermicompostscontrasting
confidence: 93%
“…These results are also in agreement with Rengarajan, Melanathuru [68] who noted that M. oleifera contains flavonoids among other phytochemicals. Legumes exude specific flavonoids that act as signalling molecules to attract N-fixing bacteria [78], which is essential in making N available in the soil for plant use.…”
Section: Microbial and Earthworm Populations In Vermicompostssupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, Turkyılmaz (2013) reported cyanidin-3,5-diglucoside as major anthocyanins present in the PJs of Turkey varieties and PJ also contains cyanidin-3-glucoside, delphinidin-3-glucoside, pelargonidin-3-glucoside, delphinidin-3,5-diglucoside, and pelargonidin-3,5-diglucoside [53]. The content of anthocyanin and antioxidant property of methanolic extract of Po has already been reported [54]. Borochov-Neori et al (2011) reported the effect of climate on the composition of anthocyanin and its content Po fruit arils [55].…”
Section: Resultsmentioning
confidence: 84%